Reflection Center for suspended Histories : An attempt (The Reader). - Biennale Venetië 2013; Mihulet, Anca; Dan, Liviana; Flores, Patrick D.; Vlasiu, Ioana; Wucher, Monica; Hamadeh, Rana; Badovinaac, Zdenka (Bucharest : Romanian Cultural Institute, 2013)
Apparatus 22 ; Botea, Irina ; Ilfoveanu, Nicu ; Bregula, Karolina ; Matei, Adi ; Mihaltianu, Olivia ; Moldovan, Sebastian
Tentoonstelling'Reflection Center for suspended Histories. An Attempt', Romanian Pavilion, 5th International Art Exhibition La Biennale di Venezia, 01.06.2013 - 24.11.2013.
boek
Keywords: Roemenië